The primary controlling factors of the occurrence state of deep high-rank coalbed methane in eastern Ordos Basin - Shi, Yujiang; He, Yufei; Wan, Jinbin; Sun, Jianmeng; Zeng, Jingbo; Cui, Ruikang (Frontiers in Earth Science, 2024)
This study investigates the key controlling factors of the occurrence state of deep coalbed methane (CBM). CBM is an abundant energy resource in China, particularly in deep coal seams. However, the exploration and development of deep CBM face numerous challenges, and the understanding of the controlling factors of its occurrence state is still limited. The study reveals that deep CBM primarily exists in the form of adsorbed gas and free gas within the pore-fracture system of coal. Factors such as formation temperature, formation pressure, pore structure, and water saturation collectively influence the occurrence state of deep CBM. By employing the Simplified Local Density (SLD) model and molecular simulation methods, this study examines the impact of two external geological control factors (formation temperature, formation pressure) and three internal geological control factors (pore size, water saturation, Specific surface area) on deep CBM and establishes a theoretical model for gas content. Finally, the relationship between the adsorbed gas, free gas, total gas content, and burial depth is calculated using the model, uncovering the primary factors controlling the occurrence state of deep CBM. This research is of significant importance in providing key parameters for gas content in deep coal and optimizing deep CBM exploration.